Characterization of attenuation parameters at a variety of scales in volcanic rocks - Di Martino Perez, María Del Pilar (Curtin University, 2022)
Seismic imaging through heterogeneous structures is especially challenging in volcanic environments, in which an important portion of the seismic data is attenuated by scattering and absorption. This thesis explores the connection between attenuation and scattering parameters with volcanic rock properties (petrophysical/mineralogical) and lays down the use of these parameters to develop new imaging techniques. The findings show the relevance of including stochastic attenuation parameters in the characterization of heterogeneous settings as a necessary step to interpret observations in the field.